Green marketing: Purchasing decision of housewives towards eco-friendly - Castillo, Sofia., Gaddi, Daniel., Lecap, Monique Jennine., Sun, Joyce Caila., Tayoto, Aecelle 4 0 16; 5
Abstract This study examines the marketing factors influencing the housewives purchasing decisions towards eco-friendly products, focusing on price, preference, convenience, and promotions. Quantitative data was collected through surveys and questionnaires, allowing for an analysis of the relationships between these factors and housewives decision-making processes. The study reveals that demographic and financial factors significantly affect the marketing factors influencing housewives decisions. Price, preference, convenience, and promotions emerged as key influencers in housewives eco-friendly product choices. These findings contribute to a deeper understanding of consumer behavior and provide insights for businesses and marketers in promoting eco-friendly products. Keywords: eco-friendly products, marketing factors, price, preference, convenience, promotions, demographic profile, financial planning, purchasing decision, and consumer behavior
Business Research: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2